Long-term outcomes from critical care. Issue 4 (April 2018) - Morgan, Amy; O'Connor, Laura
Abstract: With the improved survival of critical care patients, a cohort of chronically critically ill patients has emerged. These patients have a higher 5-year morbidity and mortality and greater utilization of healthcare resources. This well-documented deterioration in physical, cognitive and/or psychological health in critical care survivors is known as post intensive care syndrome (PICS), which has personal and socioeconomic implications not only for the patient but for their families, care givers and society. Greater awareness of the impact of critical illness on quality of life has led to the emergence of research focused on overall patient outcomes rather than crude survival. Contemporary national guidelines state personal rehabilitation programmes involving a multidisciplinary team should be commenced within 24 hours of admission and continued after discharge to the ward. Once discharged home, specialist ICU follow-up clinics are key in identifying any long-term complications of critical care admission and should focus on all aspects of the PICS.